2013
DOI: 10.11648/j.cmr.20130204.18
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and Correlates of Tuberculosis among HIV Patients at Felege Hiwot Referral Hospital, Bahir Dar City, Northwest Ethiopia

Abstract: Abstract:Background: Tuberculosis and HIV have been closely linked since the emergence of AIDS. The aim of this study is to assess magnitude of Tuberculosis and its associated factors among HIV patients at Felege Hiwot Referral Hospital in Bahir Dar city. Methods: Institutional based Cross-sectional study was conducted in September 2012 in Bahir Dar city. Systematic sampling technique was employed to collect the data; both primary and secondary data were collected by interviewing HIV cases and reviewing their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 8 publications
(8 reference statements)
5
13
0
Order By: Relevance
“…This clearly shows that TB coinfection increases in HIV positive individuals with decrease in CD4 cell count. Similar observations were done by some studies where CD4 cell counts were <200cells/mm 3 and severe immunosuppression in HIV/TB co-infected individuals when compared to HIV infection alone (Kamath et al, 2013;Belay et al, 2013;Taha M Deribew et al, 2011;Giri et al, 2013;Maruza et al, 2011). It is also important to detect MDR-TB in India where TB is endemic with a prevalence of 3% in new cases and 12-18% in old tested cases (Chauhan, 2008) the sensitivity of sputum microscopy will be less in HIV/TB coinfection but can be detected better by CBNAAT.…”
Section: Resultssupporting
confidence: 82%
“…This clearly shows that TB coinfection increases in HIV positive individuals with decrease in CD4 cell count. Similar observations were done by some studies where CD4 cell counts were <200cells/mm 3 and severe immunosuppression in HIV/TB co-infected individuals when compared to HIV infection alone (Kamath et al, 2013;Belay et al, 2013;Taha M Deribew et al, 2011;Giri et al, 2013;Maruza et al, 2011). It is also important to detect MDR-TB in India where TB is endemic with a prevalence of 3% in new cases and 12-18% in old tested cases (Chauhan, 2008) the sensitivity of sputum microscopy will be less in HIV/TB coinfection but can be detected better by CBNAAT.…”
Section: Resultssupporting
confidence: 82%
“…Sample size was also calculated for second specific objective from the study conducted in Gondar University hospital and Felege-Hiwot Referral Hospital [13] [19]. Thus, Sample size calculated for the second specific objectives; CD4 count (>200) by considering 10% of lost to follow up, resulted 436, which is less than sample size calculated for first specific objective, so sample size (502) calculated for first specific objective was taken as sample size ( Table 1).…”
Section: Sample Size Determinationmentioning
confidence: 99%
“…The slower CD4+ cell reconstitution in older patients may be related to an impaired thymic function [18] and CD4 reconstitution has been shown to be age dependent [19,20]. In addition this study showed that 54.6% of ART patients were under the category of clinical stage equal to or above III according to WHO criteria; however this rate was lower than the study reported from Bahir Dar, northern part of Ethiopia, which was 69.7% [21]. The rates of clinical stage start to decline after using ART treatment and taking prophylaxis at baseline [22].…”
Section: Discussionmentioning
confidence: 62%